2014
DOI: 10.1021/jp503487a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced SERS Stability of R6G Molecules with Monolayer Graphene

Abstract: In this work, we used monolayer graphene, either underneath or on top of the R6G molecules, to enhance the stability and reproducibility of surface enhanced Raman spectroscopy (SERS). The time evolution of characteristic peaks of the organic molecules was monitored using Raman spectroscopy under continuous light irradiation to quantitatively characterize the photostability. Graphene underneath the organic molecules inhibits the substrate-induced fluctuations; and graphene on top of the organic molecules encaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…The highly impermeable graphene has been demonstrated for impeding the migration of liquid, gas and chemical/biological molecules [12][13][14][15][16][17] . Recently, researchers used graphene layer for preventing the reaction and inter-diffusion at the interfaces of Al/Si, Cu/Si and Au/Ni [18][19][20] .…”
mentioning
confidence: 99%
“…The highly impermeable graphene has been demonstrated for impeding the migration of liquid, gas and chemical/biological molecules [12][13][14][15][16][17] . Recently, researchers used graphene layer for preventing the reaction and inter-diffusion at the interfaces of Al/Si, Cu/Si and Au/Ni [18][19][20] .…”
mentioning
confidence: 99%
“…Another advantage to combine graphene and metallic nanostructures it that graphene can help protect molecules from photoinduced damage, such as photobleaching [19,32,60,61]. The photobleaching (or photodegradation) of the Raman analytes induced by the laser is a well-known phenomenon in normal SERS experiments, especially for dye molecules.…”
Section: Two-dimensional Materials Combined With Metallic Nanostructuresmentioning
confidence: 99%
“…When combining graphene with metallic nanostructure, the hybrid SERS platform is more stable against photoinduced damage, but with a comparable enhancement factor. Zhao et al [61] demonstrated that graphene underneath the organic molecules inhibited the substrateinduced fluctuations; and graphene on top of the organic molecules encapsulated and isolated them from ambient oxygen, greatly enhancing the photostability. Liu et al [32] fabricated graphene-encapsulated metal nanoparticles for molecule detection and found out that AuNP/graphene hybrid substrate could significantly suppress photobleaching and fluorescence of phthalocyanine and R6G molecules.…”
Section: Two-dimensional Materials Combined With Metallic Nanostructuresmentioning
confidence: 99%
“…The problems associated with photoinduced damage, including photocarbonization and photobleaching, can be effectively suppressed. Zhao et al further discussed the mechanism by which the graphene coating enhances the stability and reproducibility of the SERS signal of organic molecules . They showed that a graphene layer provides another path for the relaxation of the excited state in organic molecules and encapsulates organic molecules to prevent the reaction between the organic molecules and O in ambient conditions.…”
Section: Highly Impermeable 2d Materials Membranesmentioning
confidence: 99%